Antiviral therapy is associated with a better survival in patients with hepatitis C virus and B‐cell non‐Hodgkin lymphomas, ANRS HC‐13 lympho‐C study. Issue 3 (24th November 2014) - Michot, Jean‐Marie; Canioni, Danielle; Driss, Henda; Alric, Laurent; Cacoub, Patrice; Suarez, Felipe; Sibon, David; Thieblemont, Catherine; Dupuis, Jehan; Terrier, Benjamin; Feray, Cyrille; Tilly, Hervé; et al.
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) infection increases the risk of B‐cell non‐Hodgkin lymphomas (B‐NHL). Antiviral treatment (AT) can induce hematological responses in patients with marginal zone lymphomas (MZL). The ANRS HC‐13 Lympho‐C study aimed at a better understanding of the impact of AT on HCV associated B‐NHL. This multicentric study enrolled 116 HCV‐positive patients with B‐NHL between 2006 and 2012. Cytological and histological samples were collected for centralized review. At lymphoma diagnosis, median age was 61 years and gender ratio M/F was 1. Cytohistological distribution was marginal zone lymphoma (MZL) n = 45 (39%), diffuse large B‐cell lymphoma (DLBCL) n = 45 (39%), and other types n = 26 (22%). MZL patients had more frequent detection of rheumatoid factor (68% vs. 35%; P = 0.001) and more frequently mixed cryoglobulinemia (74% vs. 44%; P = 0.021) than patients with DLBCL. Among patients receiving AT, a sustained virologic response was achieved in 23 of 38 (61%) patients with MZL and in 9 of 17 (53%) with DLBCL (P = 0.42). Three‐year overall survival (OS) and progression‐free survival were 78% 95%CI [63–88] and 64% [48–76], respectively, without difference between cytohistological groups. Outcome analysis showed a favorable association between OS and AT in all patients (P = 0.05) and in the subgroup of MZL patients only (P = 0.04). Our data support that AT improves the outcomes of HCV‐associated NHLs. The impact of new AT regimen with protease inhibitor needs to be investigated in this setting. [clinicalTrials.govIdentification number NCT01545544] Am. J. Hematol. 90:197–203, 2015. © 2014 Wiley Periodicals, Inc.